Ecological niche modeling of the genus Papio. Issue 4 (1st April 2018) - Fuchs, Amanda J.; Gilbert, Christopher C.; Kamilar, Jason M.
Abstract: Objective: Ecological niche modeling (ENM) has been used to assess how abiotic variables influence species distributions and diversity. Baboons are broadly distributed throughout Africa, yet the degree of climatic specialization is largely unexplored for individual taxa. Also, the influence of climate on baboon phylogenetic divergence is unknown. In this study, we constructed ENMs to investigate how niches vary across Papio species to understand how climatic variables have influenced their biogeography and mode of speciation. Materials and Methods: We used Maxent to generate ENMs by collating locality data for six Papio species and climate information from WorldClim. In addition, we examined the degree of niche overlap among all possible pairs of taxa, which can provide insight into patterns of species diversity. Lastly, we conducted a Mantel test to assess the relationship between niche overlap and estimated time since divergence. Results: Our models performed moderately to extremely well, with a mean area under the curve value of 0.868. The species with the best models include P. papio and P. kindae, whereas P. hamadryas had the poorest models. We found that most species pairs exhibited significantly different niches. Lastly, we found no significant correlation between niche overlap and divergence times. Discussion: Niche models had good predictive power, which indicates Papio species distributions are correlated with climatic variables to varying degrees. Significantly little niche overlap and incomplete geographic boundaries suggests these models generally support a parapatric speciation scenario for the genus Papio .